GLOBAL PERSPECTIVES: INTEGRATING COMPARATIVE AND APPLIED LINGUISTICS - Mirzakarimova Mubinakhon Abdurakhmon kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Understanding languages requires both theoretical insight and practical application. Comparative linguistics examines patterns, structures, and relationships across languages, while applied linguistics focuses on solving real-world challenges such as teaching, translation, and communication in multilingual contexts. This article explores how these two fields intersect on a global scale, highlighting the importance of cross-linguistic analysis, language typology, and cultural context. The study finds that integrating comparative approaches into applied practices can enhance language education, translation quality, and intercultural understanding, particularly in multilingual and international settings.